Improving English Pronunciation in Primary School Students: A Study from Merah Putih English Course - Tenri Ampareng; Ricky Gazali; Sri Rahayu (Universitas Islam Negeri Palopo, 2025)
This study investigates the effectiveness of the MERAH PUTIH English course in improving pronunciation skills among primary school students. The course focuses on enhancing articulation, stress, intonation, and overall intelligibility. A mixed-methods approach was employed, involving pre- and post-tests, classroom observations, and interviews with both students and teachers. The results demonstrate significant improvement in students' ability to articulate English sounds, particularly in vowel pronunciation, word stress, and sentence intonation. Audiovisual tools, such as pronunciation apps and interactive videos, provided students with immediate feedback, which contributed to their motivation and progress. Additionally, corrective feedback from teachers and peers played a crucial role in refining pronunciation accuracy. The study highlights that consistent practice, targeted phonetic training, and the integration of modern technology significantly enhance students' pronunciation skills. The findings suggest that incorporating audiovisual tools and corrective feedback into language learning programs can be highly effective for young learners. This research contributes to the understanding of how primary school English courses can be optimized to improve pronunciation skills, with implications for language educators looking to enhance pronunciation teaching methods. The study recommends integrating phonetic exercises and speech recognition tools in future curricula to support continuous pronunciation improvement.